Muriicola soli sp. nov., isolated from soil. Issue 7 (16th July 2021) - Kang, Hye Jeong; Kim, Min-Kyeong; Roh, Su Gwon; Kim, Seung Bum
Abstract : A Gram-stain-negative, oxidase-positive, catalase-positive, aerobic, orange-pigmented, rod-shaped and non-motile bacterium designated strain MMS17-SY002 T was isolated from island soil. The isolate grew at 20–37 °C (optimum, 30 °C), at pH 6.0–9.5 (optimum, pH 7) and in the presence of 0.5–4.0 % (w/v) NaCl (optimum, 2.0 %). Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain MMS17-SY002 T was mostly related to the genus Muriicola of the family Flavobacteriaceae and had highest sequence similarity of 96.82 % to Muriicola marianensis A6B8 T and Muriicola jejuensis EM44 T, but formed a distinct phylogenetic line within the genus. Chemotaxonomic analyses showed that menaquinone 6 was the predominant isoprenoid quinone, the major fatty acids were iso-C15 : 1 G and iso-C15 : 0, and the diagnostic polar lipid was phosphatidylethanolamine. The genomic DNA G+C content was 42.4 mol%. Strain MMS17-SY002 T could be distinguished from related species by the combination of trypsin, α-chymotrypsin, acid phosphatase, naphthol-AS-BI-phosphohydrolase, α-galactosidase, β-galactosidase and β-glucosidase activities. The orthologous average nucleotide identity between the genomes of strain MMS17-SY002 T and M. jejuensis and that between the strain and M. marianensis A6B8 T were 73.26 and 73.33%, respectively, thus confirming the separation of the strain from related species at species level. Based on the phenotypic, phylogenetic, chemotaxonomic and genomic characterization, MMS17-SY002 T should be recognized as a novel species of the genus Muriicola, for which the name Muriicola soli sp. nov. is proposed. The type strain is MMS17-SY002 T (=KCTC 62790 T =JCM 32370 T ).